(Ba, Sr)TiO3/polymer dielectric composites–progress and perspective. (August 2021) - Gao, Feng; Zhang, Kena; Guo, Yiting; Xu, Jie; Szafran, Mikołaj
Abstract: This paper reviews recent developments and challenges of (Ba, Sr)TiO3 /polymer functional composites. The microstructure of barium-strontium titanate (Ba, Sr)TiO3 (BST)/polymer composites with different polymer matrices and the nature of the interface between the BST and polymer matrix is critical in the final dielectric properties. The effects of concentration, particle size and BST filler shape on the dielectric properties of BST/polymer composites are discussed. A theoretical model for the dielectric constants of ceramic/polymer composites and the fabrication of BST/polymer composites are described briefly. The development of a dielectric tunability for the BST/polymer composites is summarized. A dielectric tunability theoretical model is proposed based on our previous research results and the effects of several factors on the dielectric tunability of the composites are discussed, which contributes to a prediction of the dielectric tunability of the composites and provides important theoretical and research significance for future work.